ANALISA KEPUASAN MAHASISWA PROGRAM STUDI TEKNIK LISTRIK POLITEKNIK NEGERI MALANG TERHADAP PELAYANAN AKADEMIK, PROSES BELAJAR MENGAJAR (PBM) DAN PRAKTIKUM - Sigit Setya Wiwaha; Khrisna Hadiwinata; Rokiyah; Mudjiono (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2022)
College as one of the institutions engaged in education is expected to be able to produce graduates who are able to answer the challenges and needs of the market. To meet these demands, universities must be able to improve their ability to educate students so that they can meet the expectations of stakeholders. This study aims to determine whether the Academic Service, Teaching and Learning Process (PBM) and Practicum in the electrical engineering study program have been able to meet expectations and provide satisfaction to students. The benefits of the results of the research are expected to provide an overview of the results of the measurement process which can later be used to improve service quality continuously so as to meet student expectations.